Miejsce procesu cywilnego w systematyce prawa rzymskiego - Czech-Jezierska, Bożena Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
There are numerous and highly interesting problems and questions arising from the Roman law of civil procedure. We might have, for instance, some doubts becouse of public or private character this procedure. The article presents some controversial and selected issues considered with position of civil procedure in the sistematization of Roman law. The system of the law of procedure in ancient Rome had its own dynamic evolution down to Justynian period. The most important for the didactic purpose seems to be the Roman formulary procedure, which was intricate an has attracted the same admiration as Roman private law. The Roman had never gathered this procedure sistematically or studied it as an autonomous subject. The Roman law of civil procedure, in spite of its fundamental influence on the development and structure of the Roman system of private law, is usually confined to a chapter in textbooks on Roman law. The right way of enunciate this part should helps the students to understand the historical background of present trends in civil procedure and to appraise the humanistic factors working in them.